Ocean remote sensing technologies : high frequency, marine and GNSS-based radar - Huang, Weimin; Gill, Eric William, 1956- (Radar, sonar and navigation, 2022)
The book provides a systematic introduction to the principles, state-of-the-art methods and applications of high frequency surface/sky wave radar and microwave marine radar, as well as an exploration of ongoing challenges in the field. It is a valuable resource for the radar and remote sensing communities.